Dataset on the Acceptance of Islamic Microfinance in Kano State, Nigeria - Surajo, Musa Yakubu; Asmadi, Mohamed Naim; Noraini, Yusuff (Elsevier Inc., 2021)
The present data from 194 customers of small and medium enterprises (SMEs) is about their acceptance of Islamic microfinance in Kano State, Nigeria. The dataset includes variables such as gender, age, marital status, duration as customer, account operate, annual income, type of business, service quality, perceived value, corporate image and religiosity of customers in Kano State. A survey from March to June 2019, self-administered questionnaires were used for data collection. This data may help scholars to understand how people of Kano State accept Islamic microfinance interacted with service quality, customer perceived value, corporate image and religiosity